2-DOF Lead-Plus-PI Control Approach For Magnetic Levitation System - Soon, Allan Chan Roong; Chong, Shin Horng; Said, Mohamed Azmi (Penerbit Universiti, UTeM, 2016)
This paper proposes Two-Degree of Freedom (2-DOF) Lead-plus-PI a classical linear control system for positioning control of a magnetic levitation (maglev) system. Maglev system has practical importance in many engineering system. However, maglev has inherently nonlinear and open loop unstable characteristics. Thus, it is a challenging task to control the maglev system. In this paper, the 2-DOF Lead-plus-PI controller is developed to control the positioning performance of the maglev system as it has simple control structure and straightforward design procedure that can be designed using root locus technique and Ziegler Nichols second method. The proposed controller can be easily implemented into the maglev system without require deep knowledge in control system. The effectiveness of the proposed controller is validated experimentally. Experimental results show the 2-DOF Lead-plus-PI controller has a better positioning accuracy and transient response in point-to-point motion, as compared to Lead-plus-PI controller. The proposed controller shows a position accuracy of 40 μm, which is around the vibration amplitude of the sensor output in open loop. It also takes less than 1 second to stabilize the ball within ± 200 μm and the steady state error has improved to around 45% in point-to-point positioning performance. Besides, the proposed controller also reduced the tracking error to about 48% as compared to Lead-plus-PI controller.